Synoptic Control of Contrail Cirrus Life Cycles and Their Modification Due to Reduced Soot Number Emissions. Issue 21 (11th November 2017) - Bier, A.; Burkhardt, U.; Bock, L.
Abstract: The atmospheric state, aircraft emissions, and engine properties determine formation and initial properties of contrails. The synoptic situation controls microphysical and dynamical processes and causes a wide variability of contrail cirrus life cycles. A reduction of soot particle number emissions, resulting, for example, from the use of alternative fuels, strongly impacts initial ice crystal numbers and microphysical process rates of contrail cirrus. We use the European Centre/Hamburg (ECHAM) climate model version 5 including a contrail cirrus modul, studying process rates, properties, and life cycles of contrail cirrus clusters within different synoptic situations. The impact of reduced soot number emissions is approximated by a reduction in the initial ice crystal number, exemplarily studied for 80%. Contrail cirrus microphysical and macrophysical properties can depend much more strongly on the synoptic situation than on the initial ice crystal number. They can attain a large cover, optical depth, and ice water content in long‐lived and large‐scale ice‐supersaturated areas, making them particularly climate‐relevant. In those synoptic situations, the accumulated ice crystal loss due to sedimentation is increased by around 15% and the volume of contrail cirrus, exceeding an optical depth of 0.02, and their short‐wave radiative impact are strongly decreased due to reduced soot emissions. These reductions are of little consequence in short‐lived and small‐scale ice‐supersaturated areas, where contrail cirrus stay optically very thin and attain a low cover. The synoptic situations in which long‐lived and climate‐relevant contrail cirrus clusters can be found over the eastern U.S. occur in around 25% of cases. Key Points: Life cycle of contrail cirrus clusters controlled by synoptic situation and therefore very variable Lower initial ice crystal number concentration can initially cause larger contrail volume but radiative impact is nearly always reduced Mitigating the contrail cirrus climate impact by reducing soot number emissions is very efficient in large‐scale ice‐supersaturated areas